Recreation in the job satisfaction of the administrative collaborators of the Private Leonardo Da Vinci University - Niño Becerra, Leslie Melissa (Espergesia, 2021)
The research was carried out in 2014 at the Leonardo Da Vinci University in the city of Trujillo, in order to determine if there is a relationship between work recreation and job satisfaction of the administrative collaborators of the Leonardo Da Vinci University of Trujillo, Peru. It is descriptive and the sample was 31 administrative collaborators; product of the same, it was corroborated that, in fact, there is a relationship between recreation and employee job satisfaction. Finally, links of friendship and teamwork could be observed in some areas, as well as shortcomings regarding motivation, work environment, joy, coaching, friendship and fe-llowship in this study group. The research concludes with a proposal of work recreation to be applied in collaborators responding to their wishes and expectations, to improve their job sa-tisfaction, personal and professional.